MÚSICA E INFANCIA: DE LA SOCIALIZACIÓN AL CONTROL SOCIAL. UN BALANCE TEÓRICO METODOLÓGICO - Marín Hernández, Juan José (2011)
The article approaches, from a review bibliography, the possibilities of realizing so much a social history of the childhood as of the infancy, across the own sources of the social history of the music. This way in the work there develops an offer that attends to the so called interdisciplinary one and of collaborative analysis that observes in these fields a working space more than the creation of a new sector historiográfico. For it, the central aim of this work is to analyze the writings that have visualized the relation between music, history, socialization and social control each of them framed inside an interpretive field who tries to understand and to interpret how there is carried out the socialization of the children and the girls outlined in the song-books and in the school music and should determine which were the processes and mechanisms that must be observed to perceive the infantile sociableness with a perspective of social paths, with his changes, transformations and continuities.